Living in Congruence with Values of the Gospel in the Aspect of Simplicity of Teachers who are Responsible for Catholic Association in Education Section of Chanthaburi Diocese. - Mariaphatthanakit, Sirawich; Phongsiri, Chartchai; Pitoyo, Agustinus Sugiyo; Suksamran, Nantapon; Prasutsaengchan, ALaddawan (Saengtham College Journal, 2021)
This research were to study : 1) Life in accordance with the gospel value on the simplicity of teachers who were responsible for Catholic Association in Education Section of Chanthaburi Diocese 2) Problems and obstacles in living the life in accordance with the gospel value, and 3) Orientation for the development on life in accordance with the gospel value. This research used mixed methods of quantitative data and qualitative data. The population used for quantitative was comprised of 94 teacher who were responsible for Catholic Association in the Education Section of Chanthaburi Diocese. The tool used for data collection was a questionnaire. The statistics used for data analysis were frequency, percentage, mean, and standard deviation. The experts were three Catholic priests obtained by purposive sampling. The tool used for qualitative data collection was semi-structured interviews. The collected data was analyzed of content analysis. The study results were as follows: 1. Living in accordance with the gospel value on the simplicity of teachers who were responsible for Catholic Association in Education Section of Chanthaburi Diocese, as a whole, was at a high level. The individual aspects which were put in descending order based on their average scores were as follows : The aspect of the gospel value of simplicity, the aspect of living a simple life in accordance with teachings of the church, and the aspect of living a simple life in accordance with the value of the Kingdom of God. 2. Problems and obstacles in living in accordance with the gospel value were as follows : (1) attitudes and priorities towards living (2) circumstances of societies amids consumerism, and (3) financial problems. 3. Orientation for the development on a life in accordance with the gospel value were as follows : (1) Teachers should adjust their attitudes and awareness of living the simple life value (2) School administrators should be good models in order that teachers would imitate and develop their simplicity in life, and (3) School should urge/mobilize teachers to develop a simple style of life in accordance with the gospel value through various activities.